SISTEM KONTROL LAMPU OPERASI TERHADAP BRIGHTNESS (LOW, MEDIUM, HIGH) BERBASIS ARDUINO UNO - Manurung, Kesaktian; Yanti, Nelly; Alrasyad, Muhammad Iqbal (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2022)
The operating lamp is one of the medical devices that has a very important role in the world of health, especially in hospitals when performing surgery. The purpose of this study was to determine the design of operating lamps for Arduino Uno-based Brightnees. To find out the low, medium, high light settings when in operation. Type of Research This research uses an experimental research type. By measuring, testing and collecting data directly at a distance of 70 meters & 100 meters using a Bh1750 sensor and compared with Lux Meter measurements on the design of operating lamps on Arduino Uno-based brightnees. The results obtained From the measurements that have been carried out using the Bh1750 sensor 5 times at a distance of 70 & 100 meters, the authors get an average, low distance of 70 M: 201.2, low distance of 100M: 43.4. Medium distance 70M: 824.2 medium distance 100M: 242.4. And high distance 70 M: 1,311.8 high distance 100 M: 700. The conclusion obtained from this study is that the farther the distance of light from the object, the less amount of light appears, and conversely, the closer the intensity of light to the object, the greater the amount of light. emerging.